Neutralization of the Tap/Trill Contrast in the Bilingual Creole-Spanish Community of the Archipelago of San Andres, Colombia - Restrepo-Ramos, Falcon (Íkala, Revista de Lenguaje y Cultura, 2022)
This study examines the segmental duration of non-vibrant rhotics in a language contact scenario in the Western Caribbean, where an English-based Creole co-exists with Spanish: The Archipelago of San Andres, Colombia. The unexplored phenomenon of the neutralization of the tap/trill contrast merits a thorough analysis to examine the effects of language contact in this Creole-Spanish bilingual population. To do this, the segmental duration of 619 non-vibrant, intervocalic taps and trills were compared in three generations of Raizal Spanish (the bilingual Spanish variety) and contrasted with the duration of Continental Spanish (the monolingual variety spoken by Colombian immigrants from Continental Colombia). While there are language-specific differences in rhotic duration between Creole and Spanish, results show that Raizal Spanish has longer durations that differ from the monolingual Spanish variety. A cross-generational examination revealed that the neutralizations of the tap/trill contrast in older bilinguals, as third-generation speakers, are converging toward the monolingual variety, distancing themselves from the older second and first generations. This phenomenon signals a change in progress resulting from diverging variation patterns of duration in tap/trill segments in generations of bilingual Raizales. These findings suggest a changing sociolinguistic panorama in which stable bilingualism is taking place among younger individuals.